2016
DOI: 10.1038/nphys3826
|View full text |Cite
|
Sign up to set email alerts
|

Physical realization of a quantum spin liquid based on a complex frustration mechanism

Abstract: Unlike conventional magnets where the magnetic moments are partially or completely static in the ground state, in a quantum spin liquid they remain in collective motion down to the lowest temperatures. The importance of this state is that it is coherent and highly entangled without breaking local symmetries. Such phenomena is usually sought in simple lattices where antiferromagnetic interactions and/or anisotropies that favor specific alignments of the magnetic moments are frustrated by lattice geometries inco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
247
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(267 citation statements)
references
References 50 publications
20
247
0
Order By: Relevance
“…It provides the source of highly frustrated magnetism that leads to the quantum spin liquid behavior observed in Ca 10 Cr 7 O 28 as described by C. Balz et al in Ref. [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides the source of highly frustrated magnetism that leads to the quantum spin liquid behavior observed in Ca 10 Cr 7 O 28 as described by C. Balz et al in Ref. [13].…”
Section: Resultsmentioning
confidence: 99%
“…Our recent experimental investigation has however revealed that this compound has very interesting magnetic properties. It realizes a quantum spin liquid ground state [13] which is a topologically ordered state where the spin moments never become static but remain in collective motion down to the lowest temperatures. Spin liquids are undergoing a lot of theoretical investigation currently however very few physical realizations exist, thus Ca 10 Cr 7 O 28 provides an important addition to our current understanding of these novel states.…”
Section: Introductionmentioning
confidence: 99%
“…The system can only be driven to a topological phase by an external factor such as an external magnetic field applied perpendicular to the kagomé plane, which can be written as H Z = −B · i S i , where B = gµ B B zẑ , g is the g-factor and µ B is the Bohr 0 0.5 1 magneton. The out-of-plane Zeeman magnetic field has a profound effect on frustrated magnets with QSL phases as it can induce a LRO [36][37][38]. In the ordered regime we find that the Zeeman magnetic field induces a noncoplanar magnetic spin texture with an emergent scalar spin chirality given by (see Ref.…”
Section: Arxiv:160804561v12 [Cond-matstr-el] 16 Jan 2017mentioning
confidence: 89%
“…Hence, the DMI suppresses the QSL phase of frustrated kagomé antiferromagnets up to a critical value [30]. The syntheses of materials have shown that various experimentally accessible frustrated kagomé antiferromagnets show evidence of coplanar/noncollinear q = 0 LRO at specific temperatures [29][30][31][32][33][34] [36] are fragile in the presence of applied magnetic field or pressure and they show evidence of LRO [37,38]. However, the role of DMI and magnetic field in frustrated kagome magnets has not been investigated in the context of thermal Hall effect and topological spin excitations.…”
mentioning
confidence: 99%
“…Their detection, however, remains a central challenge for condensed matter physics [6], and relies on the presence of quantum entanglement in their ground state and fractional quasiparticles in their excitation spectra. While the former can be checked by numerics [7], the latter can be experimentally detected by thermodynamic techniques [8][9][10] or spectroscopic probes such as inelastic neutron scattering [11][12][13][14][15][16][17] and electronspin resonance [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%